Absorbable self-reinforced polylactide (SR-PLLA) rods vs rigid rods (K-wire) in spinal fusion: an experimental study in rabbits - EROL, BÜLENT (SPRINGER, 2005)
Several clinical and experimental reports have evaluated the spinal application of bioabsorbable material for plating the anterior lumbar and cervical spine, and in anterior and posterior lumbar interbody spinal fusion. Nevertheless, the use of these materials in posterolateral interlaminar fusion has yet to be elucidated in the literature. The effects of bioabsorbable self-reinforced polylactide rod (SR-PLLA) implantation, rigid fixation (K-wire) and non-implantation with posterior interlaminar fusion were compared using a rabbit model. Twenty-four mature domestic rabbits were divided into three groups. Eight received implantation with SR-PLLA, eight with K-wire, and eight were fused without instrumentation. The animals were killed at 12 weeks and evaluated by posteroanterior radiography, manual palpation and histological examination for the presence of fusion. Successful fusion was achieved in all of the animals in both implanted groups (SR-PLLA and K-wire), whereas solid fusion was not detected in any of the specimens in the non-implanted group. Computed tomography (CT) scans were used to detect fusion mass volume. The fusion mass in the SR-PLLA implanted group had a mean volume of 1,196 mm(3)+/- 167 mm(3) vs 1,061 mm(3)+/- 181 mm(3) for the K-wire implanted group (not significant) and 711 mm(3 +/-)407 mm(3) (p < 0.05) for the non-implanted group. The results of this study suggest that the stabilization properties of both SR-PLLA rods and K-wire seem to be sufficient for spinal fusion, but using SR-PLLA is especially advantageous, since they do not require a removal operation and do not interfere with magnetic resonance imaging (MRI).
Keywords: polylactide (PLLA) rod; spine fusion; experimental; LUMBAR INTERBODY FUSION; FRACTURE FIXATION; BONE-MARROW; PINS; SCREWS; DEGRADATION; OSTEOTOMIES; IMPLANTS